2016
DOI: 10.1111/1468-5922.12260
|View full text |Cite
|
Sign up to set email alerts
|

A Strange Fire: an exploration of psycho‐spiritual development aided by Jungian analysis and Vedanta

Abstract: This paper explores the process of psychological and spiritual development through a series of active imaginations arising from the author's 'psycho-spiritual quest', a process of transformation in which the individual progressively frees themselves from the ego's identifications and may be afforded a vision of the 'self as consciousness', as described by Vedanta. The author describes how this quest was facilitated by the disciplines of Transcendental Meditation, Jungian analysis and Vedanta, and how these thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Sagar, with West (2016) presented an excellent example of integrating primary consciousness through Transcendental Meditation, Jungian analysis, and Vedantic understandings to engage the void in the Self. There is a transcendent moment of Sagar’s acceptance of the Void, as West’s commentary explains: ‘What he finds there, to his surprise is the sacred, the numinous, the awesomeness of the self’ (Sagar & West 2016, p. 629). This detached state is obtained by asking one’s self who/what is this conscious awareness?…”
Section: Non‐dualistic Consciousness and The Jungian Transcendent Functionmentioning
confidence: 99%
“…Sagar, with West (2016) presented an excellent example of integrating primary consciousness through Transcendental Meditation, Jungian analysis, and Vedantic understandings to engage the void in the Self. There is a transcendent moment of Sagar’s acceptance of the Void, as West’s commentary explains: ‘What he finds there, to his surprise is the sacred, the numinous, the awesomeness of the self’ (Sagar & West 2016, p. 629). This detached state is obtained by asking one’s self who/what is this conscious awareness?…”
Section: Non‐dualistic Consciousness and The Jungian Transcendent Functionmentioning
confidence: 99%
“…If Bright wishes to insist that a particular kind of engagement with the material is essential to the process, so be it; ultimately whether the text is taken to be a piece of active imagination, a meditation or simply 'the text', is of little import. It is for these reasons that we suggested that the process is ‘akin to … active imagination’ (Sagar & West , p. 628). That said, there are clearly long passages in the Red Book where Jung is simply noting the fantasies that emerge 'in a natural manner'.…”
mentioning
confidence: 98%